Qualidade da carne de cordeiros desmamados com diferentes idades e elaboração de produtos cárneos - Viegas, Carlos Renato [UNESP] (2014)
The aim of this study was to evaluate the following attributes of the meat of lambs weaned at different ages (30, 45 and 60 days): pH, color, shear force, water holding capacity, cooking losses, proximate composition, fatty acids profile and sensory analysis, as well as the addition or not of liver in smoked sausages and kofta and their qualitative and sensorial traits. The study was undertaken in the Faculty of Agrarian and Veterinary Sciences (FCAV), São Paulo State University (UNESP), Campus of Jaboticabal, SP, Brazil. Twenty four ½ Lacaune ½ Ile de France lambs from weaning (30, 45 and 60 days) to slaughter at 32 ± 0.2 kg live weight were evaluated. The smoked sausages and kofta were prepared using lambs meat, with the inclusion or not of sheep liver in the smoked sausages (0, 10 and 20%) and kofta (0, 15 and 30%). A completely randomized design was used and data were submitted to an analysis of variance and regression analysis using the SAS statistical software (P<0.5). The weaning age had no significant effect on the meat parameters of lambs: pH at 24 hours (5.57), temperature at 24 hours (7.57ºC), color (36.30 for L*, 14.69 for a* and 3.92 for b*), shear force (3.42 kgf/cm2), water-holding capacity (53.61%), flavor (7.39) and acceptance (7.43). The inclusion of sheep liver in the smoked sausages did not change pH (5.74), color (5.74 for L*, 9.09 for a* and 8.16 for b*), water-holding capacity (64.02%), shear force (0.40 kgf/cm2 and lipid oxidation at 0 (1.06 mg malonaldehyde/kg sample) and 24 hours (1.12 mg malonaldehyde/ kg sample). The inclusion of liver in the kofta did not change the water holding capacity (58.2%), the weight loss during cooking (26.03%), odor (7.39), color (7.24), softness (8.01) and acceptance (7.75). The different weaning ages did not influence the qualitative traits of the meat and the weaning at 30 days is the most indicated because the ewes can return to estrus more rapidly, with a better ...